Mastering Canva "Kreatif Tanpa Batas untuk Siswa SMK" di SMK Roudlotul Mubtadiin Balekambang Jepara - Abror, A. Faiq; Pradana, Reyhan Dega; Mustaghfirin, Ahmad; Ardiansyah, M. Risqi; Pradita, Rasyiid Yoga; Prabawati, Chintya (Jurnal Pengabdian dan Pemberdayaan Banyuwangi (Jurnal Abdiwangi), 2025)
The development of technology requires SMK students to master effective presentation skills using technology. To overcome the difficulties of XII grade students of SMK Roudlotul Mubtadiin Balekambang Jepara in the process of preparing final project presentations, the Balekambang Jepara Polytechnic service team organized training in making Canva-based presentations. The activity aimed to improve visual design competencies and presentation techniques through a participatory approach. The training was held for one day with 30 students majoring in Automotive Light Vehicle Engineering. The material covered three sessions: (1) Visual Design Principles (slide structure and CRAP technique), (2) Presentation Techniques (body language, time management), and (3) Canva Practice (final project slide making practice). Evaluation using pre-test/post-test and project assessment showed an increase in the average score from 58 to 82, with 85% of participants achieving scores above the standard (≥75). As a result, participants were able to apply presentation design with Canva templates, organize visual hierarchy, and present presentations more confidently. This activity can strengthen the synergy and cooperation between universities and vocational schools in preparing students for the world of work